2015
DOI: 10.2147/ijn.s88285
|View full text |Cite
|
Sign up to set email alerts
|

Current applications of graphene oxide in nanomedicine

Abstract: Graphene has attracted the attention of the entire scientific community due to its unique mechanical and electrochemical, electronic, biomaterial, and chemical properties. The water-soluble derivative of graphene, graphene oxide, is highly prized and continues to be intensely investigated by scientists around the world. This review seeks to provide an overview of the currents applications of graphene oxide in nanomedicine, focusing on delivery systems, tissue engineering, cancer therapies, imaging, and cytotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 172 publications
(159 reference statements)
0
33
0
Order By: Relevance
“…17 Graphene oxide (GO) is an oxygen-containing derivative of graphene, which is a new kind of two-dimensional carbon nanomaterial. 18 Due to the large number of oxygen-containing active functional groups on its surface, such as carboxyl and hydroxyl groups, it is easy to perform the biomaterial functionalized modification by GO, so GO has good application prospects in the biomedical field. [19][20][21] Kim et al 22 synthesized GO/calcium carbonate composites that showed good cellular biocompatibility with osteoblasts and promoted the osteogenic activity of materials in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…17 Graphene oxide (GO) is an oxygen-containing derivative of graphene, which is a new kind of two-dimensional carbon nanomaterial. 18 Due to the large number of oxygen-containing active functional groups on its surface, such as carboxyl and hydroxyl groups, it is easy to perform the biomaterial functionalized modification by GO, so GO has good application prospects in the biomedical field. [19][20][21] Kim et al 22 synthesized GO/calcium carbonate composites that showed good cellular biocompatibility with osteoblasts and promoted the osteogenic activity of materials in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that BP nanosheets, particularly those with a small size, have a relatively high reactivity with water and oxygen and are easily degradable in aqueous media 40 , 49 , 50 . Other 2D materials are not readily degradable and may accumulate inside the human body, which can cause cytotoxicity, and therefore require functionalization with other materials (e.g., polyethylene glycol (PEG), chitosan or glutathione) to enable effective body clearance when they are used for in vivo applications 51 , 52 . In short, BP exhibits a wide range of tunable bandgap, high carrier mobility, high ON-OFF current ratio, ambipolar characteristic, good biocompatibility, and in vivo biodegradability, indicating its greater potential in biomedical applications, including biosensing (optical, FET and gas sensing), photoacoustic imaging, photodynamic and photothermal therapy, and drug delivery over other 2D materials.…”
Section: Fundamental Properties Of Black Phosphorus For Biomedical Apmentioning
confidence: 99%
“…They are already employed in several applications, including neural network regeneration, cancer therapy, and stem cell tissue regeneration. 79 GO sheets were incubated with the plasma of patients with seven different diseases: thalassemia (major and minor), blood cancer, diabetes, fauvism, rheumatism, and hypercholesterolemia. The plasma from pregnant women in the same gestation period and of similar age was also used to create a PPC on GO sheets.…”
Section: Disease-induced Nanotoxicitymentioning
confidence: 99%